Answer:
Step-by-step explanation:
True
Answer: C= -10
Step-by-step explanation: First step: simplify both sides of the equation
3c−2(c+10)=7c−5(c+2)
3c+(−2)(c)+(−2)(10)=7c+(−5)(c)+(−5)(2) (Distribute)
3c+−2c+−20=7c+−5c+−10
(3c+−2c)+(−20)=(7c+−5c)+(−10) (Combine Like Terms)
c + -20 = 2c - 10
c - 20 = 2c - 10
Step 2: Subtract 2c from both sides
c - 20 - 2c = 2c -10 - 2c
−c−20=−10
Step 3: Add 20 to both sides
−c−20+20=−10+20
−c=10
Step 4: Divide both sides by -1
-c/-1 = 10/-1
C=-10
Answer:
8.4
Step-by-step explanation:
42÷5
then just multiply your answer to 5 to see if it is right
We use the FOIL method here. First, Outer, Inner, and Last.
(5x)(x) = 5x^2
(5x)(-7) = -35x
(2)(x) = 2x
(2)(-7) = -14
5x^2 - 35x + 2x - 14
Now combine like terms.
5x^2 - 33x - 14.
This is the right answer because it is now in the form of ax^2 + bx + c